La informática en el consultorio odontológico y el uso de los regsitros digitales - Garbin, Artênio José Isper [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Orenha, Eliel Soares [UNESP]; Dossi, Ana Paula [UNESP]; Silva, Milene Moreira [UNESP] (Universidad Central de Venezuela, 2010)
The use of computers in dental clinics has brought many benefits to dentist, helping them in various technical, administrative and legal. This study aimed to verify whether dentist, students of the post-graduate course in Orthodontics and Implantodontia of the Brazilian Association of Dentistry (ABO), regional Araçatuba-SP, using computers and digital documentation in clinical practice. They were invited to participate in the study all 60 students enrolled in courses of Orthodontics and Implantodontia of those institutions, in the year 2007 and those who consented (n = 52) answered a questionnaire containing questions open and closed on the subject . As the profile of the participants, 64.5% are male, 51.9% are between 30-39 years of age and 48.1% completed the graduation in the 90th. A 69.3% said they didn't receive any notion of computing during graduation and 67.3% use the computer in the office, mainly for management of the same (34.3%). Regarding the use of electronic record 55.8% reported using this technology, while 44.2% denied. 32.7% do not believe that electronic records that can serve as proof of judicial and 35.7% believe that the electronic records should be archived for 20 years. It follows that most professionals use the computer in the office and also the digital records, but does not feel secure about the legal validity of such documents, unknown, including the appropriate time of its filing.

La utilización de ordenadores en las clínicas odontológicas ha traído muchos beneficios a los cirujanos dentistas, auxiliándolos en varios aspectos técnicos, administrativos y legales. Este estudio tuvo como objetivo verificar si los cirujanos dentistas, alumnos del curso de postgrado en Ortodoncia e Implantodoncia de la Asociación Brasileña de Odontología (ABO), regional de Araçatuba-SP, hacen uso de ordenador y de la documentación digital en la practica clínica. Fueron invitados a participar del estudio todos los 60 alumnos matriculados en los cursos de Ortodoncia e Implantodoncia de aquella Institución, en el año de 2007 y los que consintieron (n=52) respondieron a un cuestionario auto administrable con preguntas abiertas y cerradas sobre el tema. En cuanto al perfil de los participantes, el 64,5% son del género masculino; un 51,9% tienen entre 30-39 años de edad y el 48,1% se graduaron en los años 90. Un 69,3% afirmaron no haber recibido cualquier noción de informática durante los estudios y el 67,3% utilizan el ordenador en el consultorio, principalmente para la administración del mismo (34,3%). En cuanto al uso del prontuario electrónico un 55,8% relataron utilizar esta tecnología, sin embargo un 44,2% negaron. El 32,7% no creen que los documentos electrónicos que tienen puedan servir como prueba judicial y un 35,7% creen que el prontuário electrónico debe ser archivado por 20 años. Se concluyó que la mayoría de los profesionales hacen uso del ordenador en el consultorio y también el prontuario digital, no obstante no se sienten seguros cuanto a la validad jurídica de este tipo de documentos, desconociendo, hasta el tiempo adecuado para archivar.
Keywords: Informatics; Legal dentistry; Dental documentation; Informática; Odontología forense; Documentación odontológica